Experimental study on the damage permeability of polypropylene fiber-reinforced concrete. (7th June 2021) - Qin, Yuan; Duan, Minghan; Ma, Weili; Li, Yanlong; Zhou, Heng; Lv, Yajun; Li, Ming
Highlights: The relationship between the effective crack width of polypropylene fiber concrete and the and equivalent hydraulic gap width is studied. Damage permeability of polypropylene fiber-reinforced concrete under various water pressure conditions were studied. Taking into consideration the curvature and roughness of the cracks, the Poiseuille's law was revised. Abstract: In this paper, the damage permeability of the polypropylene fiber-reinforced concrete (PPFRC) is studied, and plain concrete (PC) is considered as the reference object. A damage cracking specimen is prefabricated by using the disc splitting test. The crack width is measured, and the effective crack width is obtained. The penetration performance of PC and PPFRC specimens after damaging and cracking were measured by using the existing damage penetration detection device. Given the actual environment of a concrete crack surface, the equivalent hydraulic gap width is obtained by inverse calculation with the cubic law. A function relationship is found between the two crack widths. Considering the influence of curvature and roughness, a correction coefficient can be introduced to modify Poiseuille's law to describe the damage permeability. The results show that the fiber content will enhance the influence of curvature and roughness on the damage permeability of concrete. Compared with the PC specimens, adding fibers will increase the correction coefficient, but a peak effect exists. The correction coefficient decreases with the increase in the water pressure, with the most evident change in the PPFRC-0.9 specimen. By contrast, the PC specimen has no obvious change. Water pressure will reduce the influence of curvature and roughness on the damage permeability.